Tests of a New Solar Flare Model Against D and E Region Ionosphere Data. Issue 5 (6th May 2022) - Siskind, David E.; Jones, McArthur; Reep, Jeffrey W.; Drob, Doug P.; Samaddar, Srimoyee; Bailey, Scott M.; Zhang, Shun‐Rong
Abstract: We present results from a suite of models designed to simulate solar flare effects on the D and E region of the ionosphere. This suite includes models of the solar spectrum, the ionosphere and of HF radiowave propagation. A central component of this system is the development of photoelectron ionization enhancement factors with higher energy resolution in the soft X‐ray spectral region that can be used to supplement existing ionization schemes currently implemented in upper atmospheric general circulation models. We tested this photoelectron model in the NCAR Thermosphere‐Ionosphere‐Mesosphere‐ Electrodynamics General Circulation Model (TIME‐GCM) and in a photochemical model of the D region. In both cases, we compared predicted flare response using two different input solar flare spectra. One is the Flare Irradiance Spectral Model (FISM) and the other is a physics based model called NRLFLARE. Our predictions for the E region were compared with incoherent scatter radar data and suggest that enhanced flux in the 1–2 nm spectral region, as indicated by NRLFLARE, is important for reproducing the observations. For the D region, we combined our theoretical results for the X1.3 flare of 7 September 2017 with ray tracing calculations that suggest 20–40 db of 6.4 MHz absorption. This agrees with previously published observations and model estimates, all of which suggest greater HF absorption than the operational D region absorption prediction model (swpc.noaa.gov/products/d‐region‐absorption‐predictions‐d‐rap). Finally, our theoretical comparison with previously published empirical models derived from very low frequency data was less clear due, in part, to large differences between the different empirical models. Plain Language Summary: Solar flares are of great interest for their effects on planetary ionospheres and radiowave propagation. Here we present a suite of models that can model flares and their terrestrial effects. We model the solar spectrum, the resulting ionization, the ionospheric consequences and the resulting effects on radiowave absorption. Our primary interest is in the ionospheric D and E regions (50–120 km altitude) which are ionized by the soft X‐ray region (energies greater than about 500 keV) of the solar spectrum. Unfortunately, this wavelength region is not well characterized compared with the longer ultraviolet wavelengths. Further, because soft X‐rays are so energetic, they produce most of their ionization not by primary photon ionization, but by secondary photoelectron impact. We compare two models of the solar spectrum and develop a new parameterization of photoelectron impact ionization to address these uncertainties. We then input these results into two different atmospheric models and compared to various previously published observations at different altitudes. Our results illustrate the key wavelength regions in the solar spectrum where more data is needed, specifically from 1 to 2 nm, and also highlight the need for new approaches toward measuring the response of the lowermost ionosphere to solar flares. Key Points: New soft X‐ray photoelectron model is used with solar flare models as input to atmospheric chemistry models Comparison with E region radar data is consistent with enhanced flux in the 1–2 nm solar spectral region D region comparisons show agreement with observed HF absorption, but large disagreement with very low frequency data